MD5 di Era Post-Kriptografi: Studi Efektivitas untuk Perlindungan Arsip Elektronik - Habiburrahman, Habiburrahman (Universitas Negeri Padang, 2025)
The transition to digital records management raises significant concerns regarding the integrity and authenticity of electronic archives. This study evaluates the effectiveness of the MD5 cryptographic hash algorithm in ensuring the integrity of electronic records in the post- cryptography era. Using a qualitative descriptive approach, various document formats were tested to observe the sensitivity of MD5 against small data changes compared to SHA-256. The results show that MD5 can detect even minimal modifications; however, its vulnerability to collision attacks remains a significant limitation. Although MD5 remains efficient and practical for low-risk applications, SHA-256 is strongly recommended for securing critical archives. This research emphasizes the need for archival institutions to gradually migrate to stronger cryptographic standards to ensure long-term data authenticity and security in electronic recordkeeping practices.